A Novel Clinical Score for Differential Diagnosis Between Acute Myocarditis and Acute Coronary Syndrome – The SAlzburg MYocarditis (SAMY) Score - Mirna, Moritz; Schmutzler, Lukas; Topf, Albert; Sipos, Brigitte; Hehenwarter, Lukas; Hoppe, Uta C.; Lichtenauer, Michael (Frontiers in Medicine, 2022)
Background: Acute myocarditis and acute coronary syndrome (ACS) are important differential diagnoses in patients with new-onset chest pain. To date, no clinical score exists to support the differentiation between these two diseases. The aim of this study was to develop such a score, in order to aid the physician in scenarios where discrimination between myocarditis and ACS appears difficult. Materials and methods: Patients with ACS (n= 233) and acute myocarditis (n= 123) were retrospectively enrolled. LASSO regression was conducted to identify parameters associated with the highest or least probability for acute myocarditis. Logistic regression was conducted using the identified parameters, score points for each level of the predictors were calculated. Cut-offs for prediction of myocarditis were calculated. Validation was conducted in a separate cohort of 90 patients. Results: A score for prediction of acute myocarditis was calculated using six parameters (age, previous infection, hyperlipidemia, hypertension, CRP, leukocyte count). Logistic regression analysis showed a significant association of total score points and the presence of myocarditis (B= 0.9078, p<0.0001). Cut-off #1 for prediction of myocarditis was calculated at ≥4 (Sens.: 90.3%, Spec.: 93.1%; 46.3% predicted probability for acute myocarditis), cut-off #2 was calculated at ≥7 (Sens.: 73.1%, Spec.: >99.9%; 92.9% pred. prob.). Validation showed good discrimination (AUC= 0.935) and calibration of the score. Conclusions: Our clinical score showed good discrimination and calibration for differentiating patients with acute myocarditis and ACS. Thus, it could support the differential diagnosis between these two disease entities and could facilitate clinical decisions in affected patients.